Odpowiedzi

2010-01-11T18:27:32+01:00
A) 9a+6b= 3(3a+2b)
b) 35c-40d= 5( 7c - 8d)
c) 48x - 24y + 54z = 2(24x-12y+27z)
d) 25 - 50a² + 75a = 25(1-2a²+3a)
e) -a + 2b - 3c
f) -14p - 20r - 4s = 2(-7p-10r-2s)
g) -21m - 35n -7 = 7(-3m-5n-1)
h) 4,5a² - 6a + 1,5 = 1,5(3a²-2a+1)
Najlepsza Odpowiedź!
2010-01-11T18:40:49+01:00
A) 9a + 6b = 3(3a + 2b)
b) 35c - 40d =5(7c - 8d)
c) 48x - 24y + 54z = 6( 8x - 4y + 9z)
d) 25 - 50a² + 75a =5 ( 5 - 10a² + 15a)
e) -a + 2b - 3c =-(a - 2b + 3c)
f) -14p - 20r - 4s =-2(7p + 10r + 2s)
g) -21m - 35n -7 =-7(3m + 5n +1)
h) 4,5a² - 6a + 1,5 = 3(1.5a² - 2a + 0.5)